DEMOCRATIC LEADERSHIP AND SCHOOL COMMITTEE ENGAGEMENT IN ENHANCING PRIMARY SCHOOL QUALITY: A QUANTITATIVE STUDY ON COLLABORATIVE SCHOOL GOVERNANCE - Nurwanti, Siti; Pudjaningsih, Wiwik (Information Technology Education Department, 2026)
This study examines the influence of democratic leadership and school committee engagement on primary school quality within a collaborative governance framework. Using a quantitative explanatory design, data were collected from 148 teachers across public primary schools in a decentralized education context. Proportional random sampling was employed, and data were analyzed using multiple regression analysis. The findings indicate that democratic leadership significantly predicts school quality and demonstrates a large substantive effect, while school committee engagement also exerts a significant and independent medium effect. The combined model explains 48% of the variance in primary school quality, suggesting that participatory leadership and structured stakeholder involvement function as complementary governance mechanisms. Democratic leadership appears to establish organizational conditions that promote instructional effectiveness and professional collaboration, whereas active school committees reinforce accountability, transparency, and community alignment. These results provide empirical support for collaborative school governance theory and highlight the importance of integrating internal leadership capacity with external stakeholder engagement in education reform. The study contributes to international discourse on participatory governance in primary education and offers policy-relevant insights for strengthening sustainable school improvement initiatives.